Is platelet responsiveness to clopidogrel attenuated in overweight or obese patients and why? A reverse translational study in mice. (29th October 2021) - Jiang, Li‐Ping; Ji, Jin‐Zi; Ge, Peng‐Xin; Zhu, Ting; Mi, Qiong‐Yu; Tai, Ting; Li, Yi‐Fei; Xie, Hong‐Guang
Abstract : Background and Purpose: Overweight or obese patients exhibit poorer platelet responses to clopidogrel. However, the mechanisms behind this phenotype remain to be elucidated. Here, we sought to discover whether and why obesity could affect the metabolic activation of and/or platelet response to clopidogrel in obese patients and high‐fat diet‐induced obese mice. Experimental Approach: A post hoc stratified analysis of an observational clinical study was performed to investigate changes in residual platelet reactivity with increasing body weight in patients taking clopidogrel. Furthermore, high‐fat diet‐induced obese mice were used to reveal alterations in systemic exposure of clopidogrel thiol active metabolite H4, ADP‐induced platelet activation and aggregation, the expression of genes involved in the metabolic activation of clopidogrel, count of circulating reticulated and mature platelets, and proliferation profiles of megakaryocytes in bone marrow. The relevant genes and potential signalling pathways were predicted and enriched according to the GEO datasets available from obese patients. Key Results: Obese patients exhibited significantly attenuated antiplatelet effects of clopidogrel. In diet‐induced obese mice, systemic exposure of clopidogrel active metabolite H4 was reduced but that of its hydrolytic metabolite was increased due to down‐regulation of certain P450s but up‐regulation of carboxylesterase‐1 in the liver. Moreover, enhanced proliferation of megakaryocytes and elevated platelet count also contributed. Conclusion and Implications: Obesity attenuated metabolic activation of clopidogrel and increased counts of circulating reticulated and mature platelets, leading to impaired platelet responsiveness to the drug in mice, suggesting that clopidogrel dosage may need to be adjusted adequately in overweight or obese patients.